EFECTOS DE LA APLICACIÓN DE PERÓXIDO DE HIDRÓGENO AL 35% Y CEPILLADO SOBRE EL ESMALTE DENTAL (2013)
Objective: to evaluate the effects on surface hardness and roughness of the whitening gel 35% hydrogen peroxide with brushed back.Methods: an experimental In vitro study was done, 40 blocks of 3 mm2 enamel of third molar teeth of the vestibular portion was smoothed with sandpaper blocks granulation from 600 to 1500, to be divided into the two methodologies, microhardness Vickers (n = 20) and Atomic force Microscopy (n = 20), and this in two groups, GC and GCC. In the GC group the whitening was done with hydrogen peroxide 35% (n = 10), in the GCC, it was performed with 35% hydrogen peroxide and brushing with toothpaste containing 1450 ppm of fluoride. ANOVA test and a post Student t test with a level of significance α=0.05, was conducted to know the differences between the groups.Results: a statistically significant difference on the number of Vickers microhardness (NDV) in the GCC group (before: 369.4 ± 19.4 NDV, after: 392.4 ± 14.2 NDV) was found, but no statistically significant difference was observed for the surface roughness (Ra), between this two groups.Conclusion: brushing with toothpaste containing 1450 ppm fluoride after dental bleaching process with 35% hydrogen peroxide maintained the stability of the surface hardness of the enamel.